Systematic study of flow vector fluctuations in √sNN=5.02 TeV Pb-Pb collisions - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Physical review, 2024)
Measurements of the 𝑝T-dependent flow vector fluctuations in Pb-Pb collisions at √𝑠NN=5.02TeV using azimuthal correlations with the ALICE experiment at the Large Hadron Collider are presented. A four-particle correlation approach [ALICE Collaboration, Phys. Rev. C 107, L051901 (2023)] is used to quantify the effects of flow angle and magnitude fluctuations separately. This paper extends previous studies to additional centrality intervals and provides measurements of the 𝑝T-dependent flow vector fluctuations at √𝑠NN=5.02TeV with two-particle correlations. Significant 𝑝T-dependent fluctuations of the ⃗𝑉2 flow vector in Pb-Pb collisions are found across different centrality ranges, with the largest fluctuations of up to ∼15% being present in the 5% most central collisions. In parallel, no evidence of significant 𝑝T-dependent fluctuations of ⃗𝑉3 or ⃗𝑉4 is found. Additionally, evidence of flow angle and magnitude fluctuations is observed with more than 5⁢𝜎 significance in central collisions. These observations in Pb-Pb collisions indicate where the classical picture of hydrodynamic modeling with a common symmetry plane breaks down. This has implications for hard probes at high 𝑝T, which might be biased by 𝑝T-dependent flow angle fluctuations of at least 23% in central collisions. Given the presented results, existing theoretical models should be reexamined to improve our understanding of initial conditions, quark-gluon plasma properties, and the dynamic evolution of the created system.
Veröffentlicht: 13. Juni 2024
Gesehen am 13.11.2024
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, I. Zanone [und 1043 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, NN ist dabei tiefgestellt